Living together: Sympathy and the practice of politics. (March 2019) - Hankins, Joseph
What place is there for sympathy in politics or politics in sympathy? This essay takes inspiration from the Japanese formulation of multiculturalism ( tabunka-kyōsei or "the living together of multiple cultures") to explore the sympathetic politics of living together. Following a group of Japanese activists on a solidarity trip to Chennai, India, the essay builds a definition of politics—the creation of venues, scenes, and opportunities in which we might practice ourselves as we want to become—that relies on the cultivation of fellow feeling. Rooted in the history and contemporary practice of Japanese activist trips to India, this essay specifies a definition of politics and sympathetic engagement that complicates recent discussions of humanitarianism and politics that tend to place these two efforts in opposition against each other.